Pengaruh Aromaterapi Lavender Terhadap Kualitas Tidur Dan Kecemasan Pada Siswa Yang Akan Menghadapi Praktik Kerja Lapangan Di Smk Kesehatan Vancanitty Kabupaten Cianjur Tahun 2022 - Siti Salma Nur Anisya; Hari Ghanesia Istiani,; Nur Eni Lestari (DIAGNOSA: Jurnal Ilmu Kesehatan dan Keperawatan, 2023)
Introduction : Aromatherapy is a way of treating disease by using odors that generally come from plants and smell nice and are called essential oils. Lavender essential oil can be used to treat insomnia, improve sleep quality and improve long-term hospital stays, as well as reduce the need for sedatives at night. Purpose: The purpose of this study was to determine the effect of lavender aromatherapy on sleep quality and anxiety in students who will face field work practices at the Vancanitty Health Vocational School, Cianjur Regency. Methods: The instruments used in this study consisted of three parts, namely SOP (Standard Operating Procedure) lavender aromatherapy, the PSQI sleep quality questionnaire and the ZSAS anxiety questionnaire whose results were known by giving the questionnaire before the lavender aromatherapy intervention was carried out and after being given lavender aromatherapy then measured the level of student anxiety decreased or increased. Statistical test using the Marginal Homogeneity Test. The population and sample in this study were 11th grade nursing students with a total of 28 students at the Vancanitty Health Vocational School. Results: The average level of students' sleep quality before lavender aromatherapy therapy was in the moderate category (60.7%) and after lavender aromatherapy therapy the average level of students' sleep quality was in the good category (75.0%). The average level of student anxiety before lavender aromatherapy therapy was in the medium category (64.3%) and after lavender aromatherapy the average student anxiety level was in the low category (75.0%). The result of the asym sig 2 tailed value is <0.01, so the hypothesis is accepted. Conclusion: There is an effect of lavender aromatherapy on sleep quality and student anxiety with a p value <0.01.